2004
DOI: 10.1210/jc.2002-021308
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Secretion and Leptin in Morbid Obesity before and after Biliopancreatic Diversion: Relationships with Insulin and Body Composition

Abstract: Obesity is characterized by increased leptin levels and insulin resistance, whereas blunted GH secretion is paired with normal, low, or high plasma IGF-I levels. To investigate body composition in human obesity and the interactions among the GH-IGF-I axis, leptin, and insulin resistance [measured with the homeostasis model assessment (HOMA) score], we studied 15 obese females, aged 23-54 yr (mean age, 42.7 +/- 2.6), with a body mass index (BMI) of 44.02 +/- 1.45 kg/m(2), who underwent treatment by biliopancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
2
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 63 publications
5
54
2
2
Order By: Relevance
“…In the diagnostic approach for GH deficiency obesity presents a great limitation since it is characterized by a low response to all provocative stimuli for GH secretion (26)(27)(28)(29)(30)(31)(32)(33). In obesity reduction in the half-life of GH (43) as well as a significant decrease in the production and secretion of the hormone have been reported (44).…”
Section: Discussionmentioning
confidence: 99%
“…In the diagnostic approach for GH deficiency obesity presents a great limitation since it is characterized by a low response to all provocative stimuli for GH secretion (26)(27)(28)(29)(30)(31)(32)(33). In obesity reduction in the half-life of GH (43) as well as a significant decrease in the production and secretion of the hormone have been reported (44).…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, GH and IGF-I secretion increased in both men and women and resulted in a partial restoration of the GH/IGF-I axis. Metabolic markers such as lipids and glucose/insulin levels have been extensively studied, while there are only two reports (24,25) examining the GH/IGF-I axis after massive weight loss (in nine and 15 subjects before and after massive weight loss respectively). The present findings based on 63 subjects seem to be in line with other studies regarding GH secretion in obese, fasting and anorectic states (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of stimulation of GH release in obese subjects by diet may promote retention of fat mass. However, studies have demonstrated that apparently all the defects in the GH IGF-I axis in obesity are reversible with diet-induced and surgical induced large weight loss (20,56,70). The recovery of the GH IGF-I axis after weight loss suggest an acquired defect, rather than a pre-existing disorder.…”
Section: Effect Of Caloric Restriction and Weight Loss On The Gh-igf-mentioning
confidence: 99%